PENGALIHAN SERTIFIKAT OBYEK SENGKETA DENGAN AKTA NOTARIS YANG DILAKUKAN SECARA TIDAK SAH DAN MELAWAN HUKUM (STUDI PUTUSAN PENGADILAN NEGERI TANGERANG NOMOR 664/PDT.G/2019/PN.TNG) - Nanda Ahimsa Dwiputra; Isyana Wisnuwardhani Sadjarwo (The Juris, 2022)
The making of the sale and purchase deed is carried out by the parties, but in its implementation problems arise when one of the parties feels aggrieved, causing a dispute. The purpose of this study is the certificate of the object of the dispute which was carried out illegally and against the law (Study of Putusan Pengadilan Negeri Tangerang Nomor 664/pdt.g/2019/PN.TNG). This research uses juridical normative research. The results of the study indicate that legal rights to land can only be carried out with a deed made before the PPAT officers to then start with the National Land Agency (BPN). If a land is found to be disputed in court (the object of the lawsuit), then the BPN through the PPAT is required not to continue making deed in writing to the interested parties. This is in accordance with Government Regulation No. 24 of 1997 concerning Land Registration Article 39 paragraph (1) letter f. The form of civil sanctions against notaries is compensation, and default can also be against acts that violate the law. The types of administrative sanctions are verbal warning, written warning, temporary dismissal, respectful dismissal, dishonorable discharge. Regarding the crime of forging letters, namely Article 263, Article 264, and Article 266 of the Criminal Code.